Economic Exchanges Management in the Exhibition Bilateral Market - K. V. Simonov (Управленческие науки, 2020)
The slowdown in Russian economy caused a drop in demand for exhibition business services. Operating in the segment of trade fairs organizing companies faced a decrease in the intensity of economic exchanges due to the outflow of customers. The paper considers modification of the exchange management in order to intensify the latter. The research methodology bases the provisions of the theory of bilateral markets, theories of management, marketing and logistics, methods of analysis and synthesis, as well as on the experience of exhibition activities. As a result of the study: the expediency of application by linear companies-organizers of the business model “two-sided market” was justified; the interpretation of business model determined by two-component functional two-stage system was given when the platform (service) is prepared within the linear fragment and then the main fragment turns on — two-sided market, providing intensification of exchanges management by means of asymmetric pricing strategies and network effects. Recommendations are formulated for practitioners who are puzzled by the problem of economic exchanges intensification. The combination of these theoretically and practically significant results develops the theory of two-sided exhibition markets, as well as provides scientific support in the format of recommendations and descriptions of tools that help exhibition business practitioners cope with the problem of managing economic exchanges.